Gut Microbiota Was Involved in the Process of Liver Injury During Intra-Abdominal Hypertension - Zhao, Zeyu; Guo, Zhengchang; Yin, Zhengliang; Qiu, Yue; Zhou, Bo (Frontiers in Physiology, 2021)
Background: Intra-abdominal hypertension (IAH) and abdominal compartment syndrome (ACS) can lead to multiple organ failure (MOF) in the abdominal cavity, and intestinal injury is considered to be the initiating factor of MOF. Intestinal damage caused by IAH/ACS can lead to the ectopic gut microbiota, which can lead to liver injure via portal veins. Therefore, it is speculated that gut microbiota disorder caused by IAH/ACS may lead to liver injury, but it has not been confirmed yet. The relationship between gut microbiota with IAH/ACS-related liver injury was investigated in this study. Methods: A model of IAH was established in rats, and 16s RNA sequencing was analyzed for gut microbiota in the feces of rats. The elimination of gut microbiota was completed by antibiotics gavage, and fecal microbiota transplantation (FMT) was used to change the composition of gut microbiota in rats. Results: In addition to the traditional cause of liver blood vessel compression, liver injury caused by IAH is also associated with gut microbiota dysbiosis. Gut microbiota clearance can relieve liver injury caused by IAH, while FMT from IAH-intervened rats can aggravate IAH-related liver injury. Conclusion: Gut microbiota mediated IAH-related liver injury through activated JNK/p38 signaling pathway.